PENGGUNAAN MIKROKONTROLER UNTUK MENDETEKSI ERROR COUNTING DAN DISTURB PADA AXLE COUNTER ALTPRO - Rahmawati, Dea Pradita; Puspitasari, Mariana Diah; Arifianto, Teguh (Jurnal Media Elektro, 2024)
Axle counter is an important component in controlling train traffic. So far, error counting and disturb disturbances can only be seen in the Equipment Room and require different handling. This study develops a tool that provides fast notification of the type of disturbance on the track to the Negative Check Officer (PNC) smartphone. This tool uses an atmega 2560, ESP8266 Wemos D1 Mini Pro, PC817 optocoupler, Light Dependent Resistor sensor, and an application created in Android studio. This study uses the Research & Development Method to produce and test the effectiveness of the product. After being tested 55 times, this tool was able to send disturbance notifications with 91% success. The average internet speed in the Equipment Room is 11.2 Mbps and on smartphones 10.10 Mbps. The average notification delivery time is 2.097 seconds. This system is expected to make it easier for PNC to handle disturbances on the track.. Keywords: Axle counter, Disturb, Error counting, Notification.